Polymorphisms of the P-selectin gene and risk of myocardial infarction in men and women in the ECTIM extension study. Issue 5 (1st November 2000) - Kee, F; Morrison, C; Evans, A E; McCrum, E; McMaster, D; Dallongeville, J; Nicaud, V; Poirier, O; Cambien, F
Abstract : BACKGROUND AND OBJECTIVE: Studies in animal models and humans implicate cell adhesion molecules in atherogenesis but their role in mediating the risk of myocardial infarction is unclear. The ECTIM (étude cas-temoin de l'infarctus myocarde) extension study was established to determine whether a previously implicated polymorphism of the P-selectin gene was associated with myocardial infarction risk in men and women in Belfast and Glasgow. PATIENTS AND STUDY SETTING: 696 cases with a recent myocardial infarction and 561 age matched controls (both male and female) were recruited into a case–control study in MONICA project areas of Belfast and Glasgow. METHODS: Demographic and lifestyle information was collected by interview administered questionnaire, and each subject was examined and provided a blood sample for DNA extraction. The polymerase chain reaction (PCR) was used to amplify regions encompassing the P-selectin Thr→Pro (A/C) polymorphism at position 715. Genotype odds ratios for myocardial infarction were estimated by logistic regression adjusted for population, age, and sex. RESULTS: There was no significant association between conventional risk factors (such as hypercholesterolaemia, increased body mass index, or raised blood pressure) and either the rare or the common Pro 715 allele of the P-selectin gene in controls. Overall, comparing Pro 715 /Pro 715 and Pro 715 /Thr 715 with Thr 715 /Thr 715, with adjustment for centre, age, and sex, the odds ratio was 0.78 (95% confidence interval 0.60 to 1.00) (p = 0.054), indicating a "protective" effect of the less common Pro 715 allele. There was no significant heterogeneity in odds ratios between men and women either in this sample or when combined with the original ECTIM subjects. CONCLUSIONS: In a large population based study in two regions of the UK, we have been able to corroborate the earlier ECTIM findings of a lower frequency of the Thr/Pro 715 polymorphism in subjects with myocardial infarction. An apparently "protective effect" of similar magnitude also seems to apply to women.